2007
DOI: 10.1021/jf071303g
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Ellagitannin-Derived Metabolites Inhibit Prostate Cancer Growth and Localize to the Mouse Prostate Gland

Abstract: Our group has shown in a phase II clinical trial that pomegranate juice (PJ) increases prostate specific antigen (PSA) doubling time in prostate cancer (CaP) patients with a rising PSA. Ellagitannins (ETs) are the most abundant polyphenols present in PJ and contribute greatly towards its reported biological properties. On consumption, ETs hydrolyze to release ellagic acid (EA), which is then converted by gut microflora to 3,8-dihydroxy-6H-dibenzo [b,d]pyran-6-one (urolithin A, UA) derivatives. Despite the accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
220
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(234 citation statements)
references
References 20 publications
10
220
0
4
Order By: Relevance
“…Furthermore, oral administration of pomegranate fruit extract to athymic nude mice implanted with androgen-sensitive CWR22RÎœ1 cells resulted in significant inhibition in tumor growth concomitant with a decrease in serum PSA levels [31]. This data was corroborated by a recent report where significant inhibition of LAPC-4 CaP xenograft growth was observed by Seeram et al, in the SCID mouse model [32].…”
Section: Pomegranatesupporting
confidence: 59%
“…Furthermore, oral administration of pomegranate fruit extract to athymic nude mice implanted with androgen-sensitive CWR22RÎœ1 cells resulted in significant inhibition in tumor growth concomitant with a decrease in serum PSA levels [31]. This data was corroborated by a recent report where significant inhibition of LAPC-4 CaP xenograft growth was observed by Seeram et al, in the SCID mouse model [32].…”
Section: Pomegranatesupporting
confidence: 59%
“…It was reported in this investigation that the all these fruit extracts except lingonberry, exhibited antiproliferative activity due to their high content of ellagitannins. Ellagitannins and ellagitannin-rich fruit extracts have also been reported earlier to inhibit cancer cell growth in other studies, possibly due to release of the potent antiproliferative compound, ellagic acid under physiological conditions (Castonguay et al, 1997;Losso et al, 2004;Larrosa et al, 2006;Misikangas et al, 2007;Ross et al, 2007;Seeram et al, 2007). On the other hand, the tannin-rich extract of lingonberry, which consisted almost entirely of proanthocyanidins, was reported to be the constituents largely responsible for the antiproliferative effects (McDougall et al, 2008).…”
Section: Polyphenolsmentioning
confidence: 64%
“…Among the studies reviewed here, there are few which have indicated antitumor activity in vivo such as topotecan (Yakushiji et al, 1997), mixture of flavonoids complexes in milk thistle (Post-White et al, 2007) and ellagic acid (Misikangas et al, 2007;Seeram et al, 2007). Raddeanin A, a triterpenoid saponin from Anemone raddeana has also demonstrated good antitumor activity.…”
Section: Mechanismsmentioning
confidence: 99%
“…Our recent study [31] showed that EA was detected in serum (134 ng/ml) and prostate (676 ng/ml) after intraperitoneal administration of pomegranate extract in mouse. It is a significant observation that EA is more targeted to prostate tissue which implies the beneficial role of pomegranate against prostate cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Our group has demonstrated that 8 ounces of pomegranate juice consumed daily following primary treatment of prostate cancer significantly prolonged prostate specific antigen (PSA) doubling time from 15 months to 54 months [30]. We have also shown that pomegranate ellagitannins suppress prostate tumor formation in a SCID mouse xenograft model [31].…”
Section: Discussionmentioning
confidence: 96%